THE STRATEGY MANAGEMENT OF RENTAL FLAT SESEP MADU ON PALANGKA RAYA CITY - Giris Ngini (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
This Research provides results of a study on the conditions of the rental flats on Palangka Raya Study Case of Sesepmadu. Here, conditions of a facility are the facility’s states of being capable of performing its intended functions. As a fundamental step in the study, this part of research provides information that should enable further steps to solving problems hampering the facilities’ full utilisation. The single block of the building consists of 96 type-21 flats. Despite being inhabited only 4 years ago, the facility has already shown decreases in its conditions. Those are related among others to the sanitary system, security, and maintenance system. Further, with the occupancy level being disturbingly low, its relation to the current conditions has been hypothesised. Perception of the residents is that there are some conditions of facilities flat are still far from expectations, the smoothness of the access roads around the neighborhood flat, area residential units flat, facilities clothes line rental public housing, clean water facilities flat, waste water disposal flat, means landfills flat, the services of the management and the participation of government in terms of management and maintenance of rental public housing facilities. It is therefore important for a future research to examine the supposed relationship and to develop an approach to improving the conditions.